2013
DOI: 10.18195/issn.0312-3162.28(1).2013.013-020
|View full text |Cite
|
Sign up to set email alerts
|

A new species of mealybug (Hemiptera: Pseudococcidae) from critically endangered Banksia montana in Western Australia

Abstract: -A new species of mealybug, Pseudococcus markharveyi Gullan sp. nov., is described and illustrated based on adult females collected from the critically endangered Banksia montana in the Stirling Range, Western Australia. A population of a possibly conspecifi c mealybug collected in 1985 from B. heliantha in Fitzgerald River National Park, Western Australia, has not been recollected despite intensive searches and may also be threatened. The new species is compared with similar mealybugs found in Australia and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
0
6
0
1
Order By: Relevance
“…Of particular interest are several species of plant dwelling insects which are specific to the Montane Heath and Thicket shrubs B. brownii and B. montana (Gullan et al . ; Taylor & Moir ).…”
Section: Methodsmentioning
confidence: 99%
“…Of particular interest are several species of plant dwelling insects which are specific to the Montane Heath and Thicket shrubs B. brownii and B. montana (Gullan et al . ; Taylor & Moir ).…”
Section: Methodsmentioning
confidence: 99%
“…4c), and there were no genetic differences between them based on the mitochondrial CO1 gene (Gullan et al . 2013). The populations were likely once part of a continuous thicket of montane heath, which stretched across the eastern massif of the Stirling Range.…”
Section: Pseudococcus Markharveyimentioning
confidence: 99%
“…Gullan et al . (2013) suggested that another population of P. markharveyi may occur in the Fitzgerald River National Park, approximately 135 km to the east, represented by specimens collected in 1985 on Banksia heliantha Mast & Thiele. Multiple attempts between 2012 and 2020 to recollect Fitzgerald River specimens for molecular work did not yield adult specimens; however, some Pseudococcidae nymphs were recovered from B. heliantha in the same area as the 1985 collection.…”
Section: Pseudococcus Markharveyimentioning
confidence: 99%
See 1 more Smart Citation
“…Debido a la complejidad reglamentaria, así como la identificación de los especímenes, la correcta detección, por medio de la descripción de caracteres, suele presentarse como un problema, principalmente cuando se deben identificar y discriminar plagas cuarentenarias de las que no lo son (Gimpel y Miller, 1996), a menos que se cuente con la opinión de un experto (Kondo et al, 2008a), o bien, se realicen distintos análisis de identificación complementaria como pruebas morfológicas y de ADN del insecto (Malausa et al, 2010;Abd-Rabou et al, 2012). Tales esfuerzos han permitido identificar nuevas especies alrededor del mundo (Kondo et al, 2005;Kaydan y Gullan 2012;Kondo et al, 2012;Gullan et al, 2013).…”
unclassified